Examine the Availability and Safety of Mucosal Cutting Biopsy Technique for Diagnosis of Gastric Submucosal Tumor - Kazuhiro Mizukami; Osamu Matsunari; Ryo Ogawa; Yuka Hirashita; Kazuhisa Okamoto; Kensuke Fukuda; Akira Sonoda; Hidetoshi Akiyama; Sotaro Ozaka; Yoshinari Kawahara; Tadayoshi Okimoto; Masaaki Kodama; et al. (Gastroenterology Research and Practice)
Objectives. Differentiating gastrointestinal stromal tumor (GIST) from other submucosal tumors (SMTs) is important in diagnosing SMT. GIST is an immunohistological diagnosis that cannot be made from images alone. Tissue sampling of tumor sites is thus becoming increasingly important. In this study, the utility and associated complications of mucosal cutting biopsy (MCB) for gastric SMTs were investigated. Methods. This was a case series study. The subjects were patients aged ≥20 years old in whom an SMT was seen on esophagogastroduodenography and who underwent MCB between January 2012 and December 2016. Patient information, endoscopy findings, gastric SMT size, pathological diagnosis, and other information were gathered from medical records. The SMT size was the maximum diameter that could be visualized on EUS. The pathological diagnosis was made with hematoxylin-eosin staining, with immunostaining added to diagnose GIST. The endpoint was the histopathological diagnostic yield. Risk assessment using the Miettinen classification and modified Fletcher classification was also done for GISTs treated with surgery. Results. The mean tumor diameter was 15.4 mm. The tumor diameter was ≥20 mm in seven patients and <20 mm in 23 patients. The tissue-acquiring rate was 93.3%. A histological diagnosis could not be made in two patients. The only complication was that bleeding required endoscopic hemostasis during the procedure in one patient, but no subsequent bleeding or no postoperative bleeding was seen. Conclusions. MCB is an appropriate and safe procedure in the diagnosis of gastric SMTs. Many hospitals will be able to perform MCB if they have the environment, including skills and equipment, to perform endoscopic submucosal dissection.